GE_GERICHTE C/23669/2014 vom 16. Oktober 2015 - GE Cour de justice (2015)
MAINLEVÉE DÉFINITIVE; CESSION DE CRÉANCE(CO); OBLIGATION D'ENTRETIEN | LP.80; LP.81; CC.289.2; CO.164; RARPA.7; LARPA.2; LARPA.3; LARPA.4; LARPA.5; LARPA.9; LARPA.10